Model Keputusan Pembelian Online Pasca Pandemi Covid-19 melalui Digital Marketing yang Dimediasi oleh Kepercayaan (Studi pada Masyarakat Kota Jambi) - Akhmad Irwansyah Siregar (Universitas Batanghari Jambi, 2023)
This study aims to analyze the effect of digital marketing on consumer purchasing decisions, both directly and indirectly through trust. The population in this study are Jambi people who have made purchases online. Where the samples taken in this study were 120 respondents. The approach in this study uses a quantitative approach with survey methods and uses Partial Least Square (PLS) data analysis. But before the analysis, the outer model was tested first through validity and reliability tests. Then do the Inner Model test through the R-Square and F-Square tests. The results of the study show that digital marketing has an influence on online purchasing decisions, both directly and indirectly through trust. This explains that if a company can maximize digital marketing then this will be able to increase public trust in a product or service. Then the trust that is formed will make people confident in deciding to buy a product. In the sense that trust is a key factor to improve purchasing decisions.